Buckling of cylindrical stainless-steel tubes subjected to external pressure at extremely high temperatures - Jo, Byeongnam; Kasahara, Naoto; Okamoto, Koji (Engineering Failure Analysis, 2018)
This study aims to experimentally investigate the buckling behaviors of stainless steel cylindrical tubes subjected to external pressure at extremely high temperatures. Buckling experiments were conducted on specimens of two different buckling modes for a wide range of pressures, specifically, from 200 to 1000 kPa in gauge pressure. The buckling temperature was measured as a function of the external pressure to examine the relationship between the buckling temperature and the external pressure. Moreover, the effect of the tube dimension (radius-to-thickness ratio) on the buckling temperature was investigated for a wide range of radius-to-thickness ratios, specifically, from 10 to 56. The buckling temperature was proportional to the external pressure and to the radius-to-thickness ratio. The measured buckling temperatures were compared with the theoretical predictions obtained from several conventional buckling models. The difference in the buckling temperatures between the experimental results and the theoretical predictions was discussed by considering the creep effect, geometrical imperfections, and a temperature dependent material property. Additionally, the buckling deformation of the stainless steel tube columns was recorded with a high-speed camera.
Keywords: Buckling deformation; Buckling experiments; Buckling temperature; External pressures; Geometrical imperfections; Radius-to-thickness ratio; Stainless steel tube; Temperature-dependent material properties; Creep; Design; External-pressure buckling; Power plant; Structural integrity